Organoprotective Properties of Argon (Review) - E. A. Boeva; O. A. Grebenchikov (Общая реаниматология)
The history of studying the organoprotective properties of argon (Ar) began in 1998 when a group of Russian researchers investigated the effect of hypoxic gas mixtures on mammalian organisms. Over several decades, evidence of the cardio-, neuro-, and nephroprotective effects of argon in various diseases and conditions in experimental models in vivo and in vitro have been accumulated. However, the lack of clinical studies to date has prompted us to carry out a systematic review analyzing the results of preclinical studies revealing organoprotective properties of argon, which could provide a rationale for its future clinical studies.The aim of this review is to describe the mechanisms of organoprotective properties of argon determined in preclinical studies.Material and methods. The search yielded 266 articles. The search algorithm was developed in accordance with the requirements and reporting guidelines for systematic reviews and meta-analysis (PRISMA) in the PubMed and Google Scholar databases. The methodology included using search queries, keywords (including MeSH), and logical operators. The keywords used for the search in the PubMed and Google Scholar databases were «argon», «ar», «protection», and «mechanism». The review included in vivo and in vitro studies.Results. The following mechanisms of argon action were identified: activation of N-terminal c-Jun kinase(JNK), p38(ERK1/2), and ERK1/2 in models of airway epithelial cells, neuronal and astroglial cell cultures, as well as in models of retinal ischemia and reperfusion injury in rats and a rabbit model of ischemia-reperfusion myocardium. Significant neuroprotective effects of argon and its influence on apoptosis were shown using small rodent models.Conclusion. The results of preclinical studies of argon have proved both its safety and organoprotective properties in in vitro and in vivo models. Analysis of the data provides a rationale for the initiation of clinical studies of argon, which could significantly improve outcomes in patients after cerebrovascular accidents, particularly post ischemic stroke.